KONSEP "WATER PALACE" DI INTERCONTINENTAL BALI RESORT - Kadek Arimbawa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2019)
The popularity of tourism in Bali has attracted tourists from all over the world to come to this a thousand temples island. There is an increase of number of tourist by 2,02 percent compare to the Julyâ€™s note in 2018 (Bali Central Bureu Statistics). As seen from the data above, there are many hotels and resort in Bali that competes to give the experience possible to the guests, one of the way is by using the Balinese architecture heritage concept â€œWater Palaceâ€. One of the resorts in Bali that has been using this kind of concept is Intercontinental Bali Resort. It is a very interesting concept using Balinese traditional architecture. The method that is used for this research is observation method on how this concept is able to attract guests to come and enjoy every corner of the resorts. The implementation of â€œWater Palaceâ€ concept is realized not only physically through the use of water element, Balinese statues, and carvings but also implemented through Hinduism philosophy in Bali.